2017
DOI: 10.1093/jac/dkx243
|View full text |Cite
|
Sign up to set email alerts
|

ESGAP inventory of target indicators assessing antibiotic prescriptions: a cross-sectional survey

Abstract: National indicators, with clear targets and incentives, are not commonly used in Europe and we observed wide variations between countries regarding the selected indicators, the units of measure and the chosen targets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 2 publications
0
25
0
5
Order By: Relevance
“…The recent position paper from the Infectious Diseases Society of America (IDSA) outlines various strategies for implementing AMS in hospital settings but lacks information on AMS interventions upon hospital discharge [ 5 ]. A recent inventory survey by the European Society of Clinical Microbiology and Infectious Diseases (ESCMID) Study Group for Antimicrobial StewardshiP (ESGAP) reported that measurable quality (appropriateness) and quantity (volume or cost) indicators in antimicrobial prescribing are lacking in several countries and that development of such indicators would lead to more appropriate prescribing [ 12 ]. Our study assessed for quality (appropriateness) and quantity (volume) of antimicrobials prescribed upon hospital discharge, a domain where there is lack of information.…”
Section: Discussionmentioning
confidence: 99%
“…The recent position paper from the Infectious Diseases Society of America (IDSA) outlines various strategies for implementing AMS in hospital settings but lacks information on AMS interventions upon hospital discharge [ 5 ]. A recent inventory survey by the European Society of Clinical Microbiology and Infectious Diseases (ESCMID) Study Group for Antimicrobial StewardshiP (ESGAP) reported that measurable quality (appropriateness) and quantity (volume or cost) indicators in antimicrobial prescribing are lacking in several countries and that development of such indicators would lead to more appropriate prescribing [ 12 ]. Our study assessed for quality (appropriateness) and quantity (volume) of antimicrobials prescribed upon hospital discharge, a domain where there is lack of information.…”
Section: Discussionmentioning
confidence: 99%
“…These initiatives provide for local surveillance of antibiotic consumption, systematic measuring, evaluating & improving quality of antibiotic usage, regular training of prescribing physicians and other relevant healthcare workers in diagnostics, treatment and prophylaxis of infections, focusing on appropriate use of antimicrobial agents as well as prevention and control of antimicrobial resistance. For example some antibiotic stewardship strategies in European countries are based on educational resources (UK and Germany), on public reporting with the data on antibiotic consumption and resistance for hospital and primary care publicly available on a website (UK) or on cross-sectoral antibiotic stewardship networks implemented in different settings (hospital, primary care, long-term care facilities) and at local, regional and national levels (Sweden France, Spain) [ 4 , 5 ]. Reliable and comparable data on the patterns of national antibiotic drug use and distribution are the starting point for analyzing the antibiotic resistance problem.…”
Section: Introductionmentioning
confidence: 99%
“…There are currently four indicators in place in France, focusing on antibiotic prescribing, and this French programme has led to an almost 4% reduction in antibiotic prescribing for these particular indicators [ 27 ]. The English pay-for-performance ‘quality premium’ programme has achieved an 8% reduction in antibiotic prescribing, without any unintended clinical consequences [ 7 , 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some countries, however, use such PIs: for example, in Belgium, an amoxicillin/co-amoxiclav ratio is used, with an 80/20 target. In England, a trimethoprim to nitrofurantoin ratio is also used, but with only a relative reduction target [ 7 ].…”
Section: Discussionmentioning
confidence: 99%